Peningkatan UMKM Melalui Pengembangan Sumber Daya Manusia di Desa Bangun Mulia Kecamatan Medan Amplas - Nurhaida, T. (Yayasan Daarul Huda Kruengmane, 2025)
This research aims to know the development strategy of SMEs through improving the quality of human resources in SMEs located in the area of Bangun Mulia Village, Medan Amplas District, North Sumatra Province. The study employed a qualitative research method. The data collection techniques in this study used observation, interviews, and documentation. Data analysis technique carried out with multiple stages namely data reduction, data presentation, and conclusion drawing. Small and Medium Micro Enterprises (SMEs) play an important role in economic growth in Indonesia. However, behind the contribution of SMEs in fostering the reeconomy in Indonesia, there are still many issues faced by SMEs in its development, both in internal and external issues. Therefore, SME development strategy becomes an important thing to make SMEs more developed. So far the issue that often arises within SMEs is the low quality of human resources. Such is the experience of SMEs in Banggun Mulia Village , Medan Amplas District , North Sumatra Province The results of the study show that the improvement of human resource quality in Mekar Sari SMEs consists of three (3) pathways. 1) Training, using the On The Job method and the Demonstration and Example method. 2) Education, using coaching and counseling methods. 3) Work Experience, with preference given to someone with work experience in recruiting employees. Improving the quality of human resources that has been applied in SMEs in Bangun Mulia Village, Medan Amplas District, North Sumatra Province has contributed to the sustainability of its business, so it can be used as a SME development strategy.